2022
DOI: 10.20944/preprints202212.0070.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diester Chlorogenoborate Complex: A New Naturally Occurring Boron-Containing Compound

Abstract: The natural compounds of boron have many applications, including as dietary supplement. Communication is based on the discovery that diester chlorogenoborate complex can be detected and quantified from green coffee bean. The study reports that such diester molecule can also be synthesized in stable form by direct reaction of boric acid and chlorogenic acid, in a mixture of acetonitrile–water (1:1, v/v), left to evaporate over a period of 48 hours, at room temperature, resulting a spirocyclic form (di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The new perspectives regarding the B essentiality for the healthy symbiosis will determine new directions for the use of B compounds, which are not digestible. An example is the recently discovered diester chlorogenoborate (DCB) complex [ 67 , 68 ] that will guide the natural B-based nutraceuticals to be used to target the human microbiome (gut, which is the most important for human health, oral cavity, vagina, skin, and scalp microbiome). In the future, we believe that indigestible B species will become essential prebiotic candidates and will ensure both the oral cavity and the colon health, as new functional foods.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The new perspectives regarding the B essentiality for the healthy symbiosis will determine new directions for the use of B compounds, which are not digestible. An example is the recently discovered diester chlorogenoborate (DCB) complex [ 67 , 68 ] that will guide the natural B-based nutraceuticals to be used to target the human microbiome (gut, which is the most important for human health, oral cavity, vagina, skin, and scalp microbiome). In the future, we believe that indigestible B species will become essential prebiotic candidates and will ensure both the oral cavity and the colon health, as new functional foods.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In fact, indigestible B, in nutrition, will target the colon and the oral cavity, and last but not least, the vagina, the skin and the scalp. Recently, B is proposed as an essential element for AI-2 synthesis of the QS system, which affects bacterial collective behavior, population density detection, virulence, biofilm production [ 68 ]. Recent studies have shown that the addition of B species to an AI-2 precursor (which is synthesized by bacteria intracellularly) generates AI-2B in the extracellular environment of the bacteria [ 67 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, B is proposed as an essential element for AI-2 synthesis of the QS system, which affects bacterial collective behavior, population density detection, virulence, biofilm production [68]. Recent studies have shown that the addition of B species to an AI-2 precursor (which is synthesized by bacteria intracellularly) generates AI-2B in the extracellular environment of the bacteria [67].…”
Section:  Conclusion and Future Perspectivesmentioning
confidence: 99%
“…B deficiency in the microbiota can cause: (i) dysbiosis, and (ii) mucus degradation, with consequences on symbiosis [6,67,68], which produces the direct interaction of host cell membranes with bacterial biofilm, and therefore their direct infection. Consequently, the microbiota needs B to achieve: (i) biosynthesis of a furanosyl borate diester (AI-2B), a part of signaling molecules family used in quorum detection; and (ii) a protective barrier that separates the microbiota from the host (B prevents direct contact between bacteria and the host organism, thus preventing the occurrence of direct infectious effects).…”
Section:  Conclusion and Future Perspectivesmentioning
confidence: 99%